Pandemi Covid-19: Eefektivitas Pembelajaran dalam Jaringan - Puji Rahayu, Tatik; Fadloli Al Hakim, Muhammad; Ibda, Hamidulloh (Al-Azkiya: Jurnal Pendidikan MI/SD, 2021)
This study aimed to analyze the implementation effectiveness of the learning from home (BDR) process during the Covid-19 pandemic in grade V of MI Muhammadiyah Botoputih Tembarak. This research used mix method. The data collection technique used was a questionnaire given to the students once a month. The subjects of this study were the students of grade V at MI Muhammadiyah Botoputih Tembarak. Based on the results of research conducted by filling out questionnaires, in general, the implementation of learning from home (BDR) in the sixth-grade students of MI Muhammadiyah Botoputih Tembarak run quite effectively with a percentage of 60-79%. The results of the BDR learning implementation questionnaire which had bad effectiveness with the criteria of 48% were in the evaluation process. It is suggested in learning from home (BDR), teachers are required to be able to design learning activities from planning to evaluating in a simpler, more creative and effective way